2021
DOI: 10.3390/catal11070806
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Flower-Shaped Copper Oxide and Nickel Oxide Nanoparticles via Capparis decidua Leaf Extract for Synergic Adsorption-Photocatalytic Degradation of Pesticides

Abstract: Green manufacturing of catalysts enables sustainable advanced oxidation processes and water treatment processes for removing trace contaminants such as pesticides. An environmentally friendly biosynthesis process produced high-surface-area CuO and NiO nanocatalysts using phytochemicals in the Capparis decidua leaf extract, which served as a reductant and influenced catalyst shape. Capparis decidua is a bushy shrub, widely distributed in dry and arid regions of Africa, Pakistan, India, Egypt, Jordan, Sudan, Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 82 publications
2
14
0
Order By: Relevance
“…Another study reported by Iqbal et al [ 168 ] showed a simple, ecofriendly, and stable synthesis of CuO and NiO nanoparticles using Capparis decidua leaf extract. The fabricated nanoparticles were analyzed using different techniques, including UV-vis, FE-SEM, XRD, and FT-IR.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported by Iqbal et al [ 168 ] showed a simple, ecofriendly, and stable synthesis of CuO and NiO nanoparticles using Capparis decidua leaf extract. The fabricated nanoparticles were analyzed using different techniques, including UV-vis, FE-SEM, XRD, and FT-IR.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…The reusability of CuO and NiO NPs against L-CHT was tested and can be for up to five runs. The results indicate the potential usage of CuO and NiO NPs photocatalysts for water treatment and the removal of pesticides [ 168 ].…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…Figure 4 shows the steps for making CuO NPs with aloe vera extract. Te above-given procedure was followed by previously reported method [55].…”
Section: Preparation Of Cuo Nps Using Alementioning
confidence: 99%
“…Furthermore, both species can generate reactive oxygen species in an aqueous solution such as superoxide (O2 − ) from dissolved oxygen reduction by Reaction ( 7) and hydroxyl radical from water oxidation by Reaction ( 8) [90]. The high reactivity of both charge carriers can be exploited in redox chemistry applied to the environment, such as water splitting by Reaction ( 9) [91,92], organic pollutants (R) oxidation according to general expression (10) [93,94], metal pollutants (M) reduction by Reaction (11) [95,96], CO2 reduction following Reactions ( 12)-( 14) [97,98], etc. A schematic of the photoelectrocatalytic degradation process can be found in Figure 11.…”
Section: Photoelectrocatalytic Applications Of Mofs In Environmental Remediationmentioning
confidence: 99%